Evaluation of Some Heavy Metals in Swertia Species Collected from Different Geographical Regions - SHAILAJAN, SUNITA; JARIPATKE, K.K.; SMRUTI, S. (Asian Journal of Chemistry, 2010)
In this paper, an attempt has been made to estimate heavy metal accumulation in an important herbal drug. Swertia and its species. Four common heavy metals Pb, Zn, Cu and Ni were analyzed by optical emission spectroscopy which uses the technique of inductively coupled plasma. Different species of Swertia are medicinally important and commonly used in various Ayurvedic formulations. Different samples of Swertia species were collected from different regions of India to compare heavy metal accumulation in them. The results indicate that metal accumulation depends both on plant species and the collection site of the plant. Swertia from Himalayan regions showed higher accumulation of heavy metals as compared to the western regions of India.